Local content game: The preferred choice for mobile learning space - Shiratuddin, Norshuhada (2009)
Two studies to find out Malaysian students’ preferences towards learning using mobile space are conducted.This first study is a survey gathered from 591 secondary school students, age 13 to 17 years old.The main objective of the survey is to acquire relevant data to support a mobile gamebased learning (mGBL) development.The outcome of this survey indicates that almost 60% of the students prefer mobile phone as the chosen platform for game-based learning rather than other devices.Further finding suggests that, in order to provide successful learning environment for students; both entertainment and education values should be embraced, suggesting mGBL as the possible solution.Also, 83% stated that they preferred local designed characters with local culture based contents.Next, the second study determines what types of game characters appeal to the students. From this, two points are concluded, which are (i) local, appealing and well-developed characters are important elements to motivate students and (ii) local uniqueness must always be incorporated to increase mGBL acceptance.